Perceived social support and depressive symptoms during the COVID-19 pandemic: A nationally-representative study. (February 2023) - Ju, Yeong Jun; Kim, Woorim; Lee, Soon Young
Background: The COVID-19 pandemic and the associated containment policies have led to negative mental health consequences in the general population. Aims: This study investigated the association between perceived social support and depressive symptoms in Korea. Methods: Data from the Korea Community Health Survey conducted from August to November 2020 was used for this cross-sectional study. Depressive symptoms were measured using the Patient Health Questionnaire-9 (PHQ-9) and perceived social support was assessed based on the number of contacts that participants had identified as being available in case participants needed isolation due to COVID-19 exposure. This study included the general adult populations aged 19 years and older. The relationship between the perceived social support and depressive symptoms was analyzed using multivariable liner regression analysis. Subgroup analysis was conducted based on income. Results: Analysis of the data obtained from 225, 453 participants indicated that PHQ-9 scores were highest in the group with 'no' perceived social support, followed by 'low', 'middle', and 'high' perceived levels of social support. Compared to individuals with 'high' perceived social support, those with 'middle' (β: .10, p -value <.001), 'low (β: .07, p -value .010), and 'no' (β: .34, p -value <.001) perceived levels of social support showed poorer depression scores. The magnitude of the relationship found was particularly strong in the low-income group. Conclusions: During the COVID-19 pandemic, individuals' depression scores varied according to their perceived level of social support. Strategies that address the need of vulnerable individuals are required to reduce the potentially negative mental health consequences of the pandemic.